From the methanol to olefins: an operational assessment. (2016) - Ali, Aaqil; Manna, Vinita; Lalchan, Kainean; Riverol, Carmen
The plant-wide process is viewed as a set of such sub-systems where a combination of several control arrangements is evaluated. In this work, the design and control of an MTO described by a rigorous dynamic model using HYSYS is assessed using different well established control combination approaches. In the first, the steady state process design and the control system are setting-up using sequential single loops. It is shown that operability is a strong function of the process design and potential operability bottlenecks are identified. In the second approach, the process design and the control system are setup using cascade and split control arrangements simultaneously leading to a better controlled system than that obtained using the sequential approach.